Atomic Layer Deposition of Titanium Phosphate from Titanium Tetrachloride and Triethyl Phosphate onto Carbon Fibers. Issue 16 (21st May 2018) - Militzer, Christian; Buchsbaum, Julia; Dzhagan, Volodymyr; Zahn, Dietrich R. T.; Wulff, Harm; Helm, Christiane A.; Goedel, Werner A.
Abstract: A thermal atomic layer deposition (ALD) process for depositing titanium phosphate onto bundles of carbon fibers as well as flat silicon and germanium substrates using titanium tetrachloride and triethyl phosphate as precursors is presented. This process yields conformal coatings on all substrates used while having a growth per cycle of 0.22 nm cycle −1, which is relatively high compared to other metal phosphate ALD processes. The reactions of the precursors with the surface are shown to be self‐limiting at 200 °C. Compositional analysis of the coating is performed using energy‐dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and Fourier‐transform infrared spectroscopy. It is shown that the as‐deposited coating has a chemical composition of Ti3.0 PO8.2 and a residual carbon content of 7%. Upon thermal annealing in air, residual triethyl phosphate and water is lost from the coating and phosphate can be identified up to 1000 °C. At temperatures exceeding 1000 °C, the coating starts to decompose. Thermogravimetric analysis of coated carbon fibers shows that the coating increases the onset temperature of the carbon fiber oxidation, thus providing an oxidation protection to the fibers. Abstract : An atomic layer deposition process for titanium phosphate using the precursors titanium tetrachloride and triethyl phosphate is shown. The half reactions are self‐limiting and conformal coatings can be obtained at a high growth per cycle of 0.22 nm cycle −1 . The chemical composition and thermal stability of the coating are investigated. The coatings provide an oxidation protection for carbon fibers.